Pengaruh Personal Characteristics Pengusaha UMKM Melalui Entrepreneurial Orientation Terhadap Kinerja Bisnis UMKM Di Kota Pasuruan - Haryono, Haryono; Muliatie, Yurilla Endah (Media Mahardhika, 2017)
Pasuruan has some excellent products produced by UMKM spread in Pasuruan City area. One of them is furniture which is commonly found in the South of Pasuruan City e.g Kelurahan Bukir, Kelurahan Sebani, Kelurahan Krapyakrejo, Kelurahan Randusari, Kelurahan Gentong, Kelurahan Petahunan and Kelurahan Karangketug. Labor is largely composed of families and neighbors around the area so that the industry can have a significant impact on improving the economy of local communities. Have a pretty good prospect to develop. The existence of micro, small and medium businesses in the Pasuruan city is a strategic industry that becomes an opportunity for improvement of the regional economy. Micro, small and medium businesses (UMKM) in addition can absorb a very large number of workers which means reducing the unemployment rate, as well as economic development. Based on the background that has been described above, the researcher choose the title of this study as follows: "The Influenced Of Personal Characteristics Of UMKMâS Entrepreneur Through Entrepreneurial Orientation To UMKM Business Performance In Pasuruan City". The type of this research is using quantitative approach, the data in the form of numbers will be analyzed using statistical methods. This type of research is causal, because it tries to know the cause or effect relationship of mutual influence between two or more variables under investigation. Population of this study is the furniture UMKMâs entrepreneurs in the Pasuruan city. The sample is 54 people of furniture UMKMâs entrepreneurs in Pasuruan city. Based on the results of research concluded that: (1) Personal Characteristics have a significant effect on the performance of UMKM business in Pasuruan city. (2) Entrepreneurial Orientation has a significant effect on business performance of UMKM in Pasuruan city. (3) Personal Characteristics have a significant effect on the performance of UMKM business in Pasuruan city through entrepreneurial orientation.